Clinical and Histological Prognostic Factors of Recurrence and Malignant Transformation in a Large Series of Oral Potentially Malignant Disorders - Lorini, Luigi; Tomasoni, Michele; Gurizzan, Cristina; Magri, Chiara; Facchetti, Mattia; Battocchio, Simonetta; Romani, Chiara; Ravanelli, Marco; Oberti, Arianna; Bozzola, Anna; Bardellini, Elena; Paderno, Alberto; et al. (Frontiers in Oncology, 2022)
BACKGROUND Oral potentially malignant disorders (OPMDs) represent a heterogeneous set of different histological lesions, characterized by the capacity to transform in oral cavity squamous cell carcinoma (OCSCC). Despite optimal surgical treatment, around 20-30% of OPMDs may evolve into OCSCC. No clear clinical / histological factors are able to identify OPMDs at higher risk of malignant transformation MATERIAL AND METHODS We considered surgically treated patients with a diagnosis of OPMDs, enrolled from 1996 to 2019 at ASST Spedali Civili of Brescia without a diagnosis of OCSCC within the previous two years. Clinical and histological characteristics were recorded. Outcomes of interest were recurrence free survival (RFS), defined as the time from surgery for OPMD to any relapse of OPMD or carcinoma, whichever occurred first, and carcinoma free survival (CFS), defined as the time from surgery for OPMD to malignant transformation. RESULTS We retrospectively reviewed 106 OPMDs cases. Median age at first diagnosis was 64 years old (IQR=18.75); female were 51.9%; of these cases. During a median follow up of 30.5 months (IQR=44), in 23.5% of patients malignant transformation occurred. RFS at 1-, 5- and 10-years was 92.4%, 60.9%, and 43.2% respectively. Female gender and history of previous OCSCC were independent risk factors for RFS. CFS at 1-, 5- and 10-years of follow-up was 97.1%, 75.9%, and 64.4% respectively. Previous OCSCC was independent risk factor for CFS. CONCLUSIONS In this large series of OPMDs, only previous diagnosis of OCSCC was a prognostic factor for further OCSCC occurrence. Given the lack of additional clinical/pathological prognostic factors, we advocate further studies into molecular characterization of OPMDs to better stratify the risk of malignant transformation.